Pengaruh Media Diorama Siklus Hidrolodi Berbasis STEM Terhadap Pemahaman Konsep IPA Kelas V - Kiki Amalia; Emy Yunita Rahma Pratiwi (IJPSE : Indonesian Journal of Primary Science Education, 2023)
The research formulated based on several obstacles including: 1) discrepancy between knowledge and skills, 2) transmissive learning, 3) the realization of the interpretation of globalization through improving education quality. This research had the purpose of knowing the effect of using STEM-based Hydrological Cycle Diorama Media for class V SDIT Ar-Ruhul Jadid. This research used the Quantitative Experiment method. The experimental research used focuses on the Quasi Experimental Design method with a Nonequivalent Control Group Design experimental model. In implementation, the class has been divided into two groups, namely the control class and the experimental class through purposive sampling technique with the requirements of the value and consideration of teacher. The results of the study stated that there was a difference between the control class and the experimental class based on mastery persentage of the control class 69% and the experimental class 81%, so it can be concluded that the Hydrological Cycle Diorama media has an effect on students' comprehension.